2016
DOI: 10.1155/2016/8568237
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisand DualM. tuberculosis/M. bovisInfection as the Cause of Tuberculosis in a Gorilla and a Lioness, Respectively, in Ibadan Zoo, Nigeria

Abstract: Tuberculosis (TB) in zoo animals is an important public health problem in places where it occurs. This is even very important in countries where there is little public health awareness about the disease; thus confined animals in the zoo can be infected directly or indirectly by infected humans and vice versa. In Nigeria, the problem of TB is a major concern among both humans and cattle. Here, we present cases of Mycobacterium tuberculosis and M. tuberculosis / M. bovis infections in a female gorilla and a lio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, the differences in the disease prevalence estimates between North and South might be influenced by the individuals' survey efforts, as most of the studies on bTB in the country were conducted mainly for academic research purposes, not to generate national data. Furthermore, although 23 States were featured in this study, the majority only had one or two reported studies, which could lead to skewed findings. Therefore, this analysis emphasizes the need for the Federal and State governments to fund surveillance efforts in all animals to demonstrate the diversity in the bTB prevalence throughout Nigeria.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the differences in the disease prevalence estimates between North and South might be influenced by the individuals' survey efforts, as most of the studies on bTB in the country were conducted mainly for academic research purposes, not to generate national data. Furthermore, although 23 States were featured in this study, the majority only had one or two reported studies, which could lead to skewed findings. Therefore, this analysis emphasizes the need for the Federal and State governments to fund surveillance efforts in all animals to demonstrate the diversity in the bTB prevalence throughout Nigeria.…”
Section: Discussionmentioning
confidence: 92%
“…More so, the most likely source of M. bovis infection to captive wildlife could be contaminated raw meat since TB has been confirmed in slaughtered livestock in Nigeria [24,25,28]. The zoo animals are at risk of exposure to M. bovis infection since the meat fed to them is not subjected to prior postmortem inspection [23]. Consequently, the risk of exposure and zoonotic transmission increases due to the endemicity of bTB in animals, and as a result, cases of human infection have been confirmed in Nigeria [13,15,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the species barrier is not strict and in rare situations M. tuberculosis can infect domestic animals, or wild animals in captivity. More than 15 species of animals can be infected with M. tuberculosis , including parrots [ 5 , 72 , 73 ]; similarly, M. africanum has been sporadically isolated from African monkeys with active tuberculosis and from cows [ 18 , 74 ]. Five MTBC have already been reported as zoonoses, causing tuberculosis in animals and transmissible to humans, including M. bovis [ 27 , [75] , [76] , [77] ], Mycobacterium caprae [ 78 , 79 ], Mycobacterium microti [ [80] , [81] , [82] ], Mycobacterium orygis [ 83 , 84 ] and Mycobacterium pinnipedii [ 85 , 86 ].…”
Section: Tuberculosis In the Animate Environment: Animalsmentioning
confidence: 99%
“…tuberculosis has emerged and persisted in elephants, with evidence of spread between elephants and to other species, including back to humans 12 23 . The emergence of M. tuberculosis in elephants, and occasional cases in other, often primate, wildlife species 24 35 , is likely due to amplification of human-wildlife contact combined with improved diagnostics, surveillance, and reporting.…”
Section: Introductionmentioning
confidence: 99%